2010
DOI: 10.1159/000319573
|View full text |Cite
|
Sign up to set email alerts
|

Wallerian Degeneration of Pyramidal Tract after Paramedian Pons Infarct

Abstract: Background: The intention of this study was the prospective analysis of Wallerian degeneration of the pyramidal tract after paramedian pons infarction. Methods: Patients with paramedian pons infarct underwent MR imaging including diffusion tensor imaging at admission and got 1–3 MR scans up to 6 months of follow-up. Clinical scores and transcranial magnetic stimulation were acquired in the acute phase and 3–6 months later. The pyramidal tracts were manually segmented in fractional anisotropy (FA) color maps af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
0
14
1
Order By: Relevance
“…However, edematous volume growth in patients with ICH was shown to be most rapid during the first 2 days after onset but to continue until day 12 postonset [26]; therefore, WD in the cerebral peduncle at 2 weeks following ICH onset may differ from CST damage at the level of the PLIC at the same stage in patients with an infarct. Moreover, Grassel et al [14] found that it was not possible to predict functional outcome according to initial DTI parameters, as the changes observed in DTI following WD are time dependent and only become apparent after several days. Therefore, predicting the potential for motor rehabilitation based on DTI parameters demands both an initial and a follow-up MRI to evaluate the individual time course of WD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, edematous volume growth in patients with ICH was shown to be most rapid during the first 2 days after onset but to continue until day 12 postonset [26]; therefore, WD in the cerebral peduncle at 2 weeks following ICH onset may differ from CST damage at the level of the PLIC at the same stage in patients with an infarct. Moreover, Grassel et al [14] found that it was not possible to predict functional outcome according to initial DTI parameters, as the changes observed in DTI following WD are time dependent and only become apparent after several days. Therefore, predicting the potential for motor rehabilitation based on DTI parameters demands both an initial and a follow-up MRI to evaluate the individual time course of WD.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional anisotropy (FA), the most widely used parameter of DTI, represents the degree of directionality of microstructures and has been used to evaluate the extent of fiber damage or changes in subcortical neural structures [11]. A decrease in the FA measurement of the involved pyramidal tract (PT) typically signifies alterations of both the CST and corticobulbar tract, which become progressively reduced during the acute-to-chronic stage of an ischemic stroke and have been shown to correlate with motor deficits [12,13,14]. In a recent study, Kusano et al [6] concluded that DTI can be used to evaluate motor deficits quantitatively and may predict the functional outcome at 28 days for patients with ICH who were scanned within 2 days of onset.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low magnification of DTI (see also Figures 4A,B) in this region only allows evaluation of large fiber tracts, such as the pyramidal tract (Grässel et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…PLI is applied for detection and segmentation as well as for morphometric analysis of these fiber tracts. Although, the analysis of the pyramidal tract is also undertaken with diffusion MRI such as for Wallerian degeneration after stroke (Grässel et al, 2010), smaller fiber tracts such as the lemniscus medialis and many others are difficult to be reliably imaged using MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Wallerian degeneration results from axonal disintegration following a stereotypical time course and is due to various pathologies including stroke [1,2] and progressive multifocal leukoencephalopathy. …”
mentioning
confidence: 99%